Tree-ring chronologies of Picea abies, Larix decidua and Fagus sylvatica along altitudinal gradients - Novak, Klemen (Les (Ljubljana), 2022)
The dendrochronological climate signal of Norway spruce (Picea abies), European larch (Larix decidua), and European beech (Fagus sylvatica), among other species, depends on altitude, therefore we have to collect dendrochronological data systematically for each species along altitude gradients. To this end, we established local tree-ring chronologies for the three species along two elevation gradients: (1) Kokra – Jezersko with sites at 750, 780, 950, 1200, 1250, 1380, 1600 m a., and (2) Bled – Radovna – Krma with sites at 518, 550, 580, 700, 750, 900, 950, 1000, 1200, 1400, 1600, 1760, 1900, 2040 m a. We present the main characteristics of the chronologies and the results of the dendroclimatological analyses, which show how the climatic factors influence the variation of the tree rings in dependence of altitude and species. We also present the agreement of the different chronologies in terms of standard dendrochronological parameters such as the t-value and discuss the potential use of the presented database.
Keywords: altitudinal gradients; branike; climate; dendrochronology; dendrokronologija; European beech; European larch; evropski macesen; Fagus sylvatica; gradient nadmorske višine; Larix decidua; navadna bukev; navadna smreka; Norway spruce; Picea abies; podnebje; Slovenia; Slovenija; tree rings